Characterization and Access to Health Care in a Reference Service for the Transsexualization Process in SUS (Research, Society and Development, 2022)
Introduction: Transsexuality is a set of ways and experiences of individuals who identify with social and sexual attributes that deviate from the gender assigned at birth. The transsexualization process is a program that makes up the Brazilian health policy and comprises a set of health care strategies, which include procedures of different degrees of complexity for the transformation process of transsexual individuals. Objective: To characterize the profile of users of a reference service, the numbers produced by the service and the main demands related to the transsexualization process. Methodology: This is a cross-sectional, descriptive and exploratory study. Data were collected through user records that are linked to the process and procedures performed by the service. Results: The data collected (N=180) indicate that a significant portion is made up of trans women (66%). Most live in the metropolitan region of Recife (81%). Regarding the age group, 65% of users are between 18 and 30 years old. Fifty-nine (59) reassignment surgeries have been performed on trans women, sixteen (16) silicone breast implants and seventeen (17) thyroplasty have been performed. In trans men, eighteen (18) underwent masculinizing mammoplasty and three (3) underwent hysterectomy. The service analyzed is the only one in the North-Northeast that offers comprehensive care to transgender people and therefore demand is high and there is a bottleneck in meeting surgical demands. Currently there is a list of approximately 580 people on the waiting list without the prospect of being welcomed.